Penatalaksanaan Holistik Wanita Usia 48 Tahun Dengan Hipertensi dan Dispepsia Melalui Pendekatan Kedokteran Keluarga - Sella Kintania Sari; Azelia Nusadewiarti (MAJORITY, 2023)
Hypertension is a condition where systolic blood pressure is ≥ 140 mmHg and/or diastolic is ≥ 90 mmHg. Dyspepsia is a collection of symptoms that lead to upper digestive tract disorders including pain or discomfort in the gastro-duodenal area, burning sensation, fullness, early satiety, nausea, and vomiting. This case report identifies risk factors, clinical problems, and provides management to patients by implementing holistic family doctor services based on evidence based medicine through a patient centered and family approach. Primary data were obtained through autoanamnesis, physical examination, and home visits to complete family data, psychosocial data, and environmental data. Secondary data was obtained from patient medical records at the Puskesmas. The assessment is based on a holistic diagnosis from the beginning, process, and end of the study both quantitatively and qualitatively. Holistic management was carried out, namely intervention using calendars, posters, and cups on a 48-year-old female patient who complained of headaches, heartburn, and nausea. The patient's internal risk factors include pre-elderly age, curative treatment patterns, overweight BMI, infrequent exercise & physical activity, inappropriate diet & eating habits, and wrong perceptions about the disease. The patient's external risk factors include stress, lack of family support and knowledge, and family history of hypertension. The evaluation obtained increased understanding of the disease and changes in behavior that have an impact on the success of therapy.